Investigation of a Novel LRP6 Variant Causing Autosomal-Dominant Tooth Agenesis - Huang, Yan-xia; Gao, Chun-yan; Zheng, Chun-yan; Chen, Xu; Yan, You-sheng; Sun, Yong-qing; Dong, Xing-yue; Yang, Kai; Zhang, Dong-liang (Frontiers in Genetics, 2021)
Background: The LRP6 (low-density lipoprotein receptor-related protein 6) gene is a recently-defined gene that is associated with the autosomal-dominant inherited tooth agenesis (TA). In the present study, a family of four generations having TA was recruited and subjected to a series of clinical, genetic, in silico, and experimental investigations. Methods: After routine clinical evaluation, the proband was subjected to whole-exome sequencing (WES) to detect the diagnostic variant. Next, in silico structural and molecular dynamics (MD) analysis was conducted on the identified novel missense variant for predicting its intramolecular impact. Subsequently, an in vitro experimental study was performed to further explore the effect of this variant on protein function. Results: WES identified a novel variant, designated as LRP6: c.2570G>A (p.R857H), harbored by six members of the concerned family, four of whom exhibited varied TA symptoms. The in silico analysis indicated that this novel variant could probably damage the dimerization and the Wnt bonding of the LRP6 protein. The experimental study demonstrated that although this novel variant did not affect the LRP6 gene transcription, it caused a defect in the maturation and phosphorylation of LRP6 protein, suggesting the loss of protein function and the disruption of the Wnt signaling. Conclusion: The present study expanded the mutation spectrum of human TA in the LRP6 gene. The findings of the present study are insightful and conducive to understanding the functional significance of specific LRP6 variants.